Strict liability for defective products: balancing of interests between consumers and producers - Amin, Naemah (Malaysian Consumer and Family Economics Association, 2007)
A system of strict liability for defective products has been incorporated into Malaysian law through Part X of the Consumer Protection Act 1999 (hereinafter referred to as the CPA). It is aimed at providing better protection to the victim of defective or unsafe products. However the system is founded on the policy consideration that product liability law should maintain a fair, just and proper balance between the interest of the consumer and the interest of the producer. Consequently liability for defective products may be strict but not absolute. A producer may free himself from liability if he furnishes proof as to the existence of certain exonerating circumstances.